A generalized entanglement-based scheme for Gaussian-modulated coherent state continuous-variable quantum key distribution. (29th May 2015) - Wang, Tianyi; Yu, Song; Zhang, Yi-Chen; Gu, Wanyi
Abstract: The source noise introduced in quantum state preparation of continuous-variable quantum key distribution (CVQKD) needs to be adequately modeled to evaluate its impact. For this purpose, we generalize the entanglement-based scheme of coherent state CVQKD from pure entangled states to mixed entangled states. In the proposed scheme, the source noise is generated via non-maximal entanglement. We prove that the proposed scheme is equivalent to a practical setup with Gaussian source noise. Furthermore, the equivalence is verified by simulation results.